2017
DOI: 10.1016/j.jcrc.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional risk assessment and cultural validation of the modified NUTRIC score in critically ill patients—A multicenter prospective cohort study

Abstract: a b s t r a c t a r t i c l e i n f o Keywords:Critically ill Nutritional risk Modified NUTRIC score Effectiveness Cultural validation Purpose: Characterize the nutritional risk of critically ill patients with the modified NUTrition Risk in the Critically ill (NUTRIC) score. Materials: National, multicenter, prospective, observational study conducted in 15 polyvalent Portuguese intensive care unit (ICU), during 6 months. Adult patients were eligible. Those transferred from another ICU or readmitted, brain dead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
50
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 17 publications
10
50
1
5
Order By: Relevance
“…The NUTRIC score was developed in studies of critically ill patient populations and has been validated in many observational studies from different countries . As IL‐6 is not routinely performed in most ICUs in the world, the modified‐NUTRIC (mNUTRIC) score without IL‐6 was proposed and revalidated .…”
Section: Nutrition Risk Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…The NUTRIC score was developed in studies of critically ill patient populations and has been validated in many observational studies from different countries . As IL‐6 is not routinely performed in most ICUs in the world, the modified‐NUTRIC (mNUTRIC) score without IL‐6 was proposed and revalidated .…”
Section: Nutrition Risk Screeningmentioning
confidence: 99%
“…Even if these variables were obtained, the accuracy of this information may not be verifiable. The variables in the final model of the NUTRIC/mNUTRIC score correlate well with the pathophysiology of malnutrition presented previously, whereby the degree of inflammation is a more determining factor of nutrition risk especially during the acute phase of critical illness and hence the use of the disease severity (Acute Physiology and Chronic Health Evaluation II) and organ failure scoring (sequential organ failure assessment) is reasonable. The variables “number of comorbidities” considered chronic inflammation and “days from hospital to ICU admission” considered iatrogenic reduced or restricted food intake that occurred before ICU admission. In our opinion, both of these variables are more objective and include the possibility of long‐term and short‐term reduced food intake and recent weight loss. The NUTRIC/mNUTRIC score has been shown in various critically ill populations to have good predictive validity for clinical outcomes, although the discriminative ability is of fair level (Table ) . Various observational studies in different populations have also shown that clinical outcomes are modified by nutrition adequacy depending on the risk status of the patients (Table ) …”
Section: Nutrition Risk Screeningmentioning
confidence: 99%
“…In 3 distinct analyses from 3 separate databases, we have shown that patients with high NUTRIC scores are less likely to die if they received closer‐to‐goal calories or protein compared with low NUTRIC score patients when there is no relationship between nutrition intake and outcome 27 – 29 . In addition, the NUTRIC score has been validated by independent investigators in Asian, Brazilian, and Portuguese populations 30 32 . In contrast, Arabi and colleagues 33 recently published a post hoc analysis of the Permissive Underfeeding versus Target Enteral Feeding in Critically Ill Adults (PERMIT) trial, where patients were randomized to different levels of caloric intake, and they analyzed the effect with high vs low NUTRIC groups of patients.…”
Section: Current Practicementioning
confidence: 99%
“…For low‐NUTRIC‐score patients, there is no relationship between nutrition intake and outcome . NUTRIC score has been validated by independent investigators in Asian, Brazilian, and Portuguese populations . In contrast, Arabi et el recently published a post hoc analysis of the Permissive Underfeeding or Standard Enteral Feeding in Critically Ill Adults (PERMIT) trial, where patients were randomized to different levels of caloric intake, and the effect with high vs low NUTRIC groups of patients was analyzed .…”
Section: Background Rationalementioning
confidence: 99%